Enhanced Efficacy of Peroxyacetic Acid Against Listeria monocytogenes on Fresh Apples at Elevated Temperature - Shen, Xiaoye; Sheng, Lina; Gao, Hui; Hanrahan, Ines; Suslow, Trevor V.; Zhu, Mei-Jun (Frontiers in Microbiology, 2019)
Peroxyacetic acid (PAA) is the most commonly used antimicrobial in spray bar antimicrobial treatment during fresh apple packing and processing. However, there are limited data regarding its practical efficacy against Listeria monocytogenes on fresh apples. This study evaluated the antimicrobial activity of PAA against L. monocytogenes on fresh apples applicable to current industry practice, and further examined practical parameters impacting its efficacy to maximize the biocidal effects. Apples were inoculated with a three-strain L. monocytogenes cocktail at 6.0 Log10 CFU/apple and then subjected to comparative antimicrobial treatments after 48 h post-inoculation. An 80 ppm PAA treatment, at 30-s and 2-min exposure, reduced L. monocytogenes on fresh apples by 1.3 or 1.7 Log10 CFU/apple, respectively. The anti-Listeria efficacy of PAA was not affected by the water hardness and pH of PAA solution, while it improved dramatically when applied at elevated temperature. A 2-min exposure of 80 ppm PAA at 43 and 46°C resulted in a 2.3 and 2.6 Log10 CFU/apple reduction, respectively. A 30-s contact time of 80 ppm PAA at 43–46°C reduced L. monocytogenes on apples by 2.2–2.4 Log10 CFU/apple. Similarly, PAA intervention at elevated temperatures significantly strengthened its effectiveness against naturally occurring apple microbiota. PAA treatment at 43–46°C can provide a vital method to improve antimicrobial efficacy against both L. monocytogenes and indigenous microbiota on fresh apples. Our data provide valuable information and reference points for the apple industry to further validate or verify process controls.